Urbanization and the changing habitat: The case of the Malay housing compound in Malaysia - Katiman Rostam,; Roslia Ahmad,; Mohd Yusof Hussain, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2006)
The process of urbanization has changed the land utilization and the function of many rural lands in the fringe areas. The rural agricultural areas have rapidly disappeared to make way for residential, industrial and commercial uses. Habitats of the originally rural population are under constant pressure from the growing urbanization and its process can be observed easily through the house’s compound. In rural Malaysia, the compound of each house is an integral part of a home garden. This study discusses the impact of metropolitan growth on the habitat of people in its surrounding areas. The Malay housing compounds in Mukim Dengkil, Selangor have been used to illustrate the change. Compounds of a total of 149 houses from 10 Malay villages in the mukim were chosen systematically. The result shows that in the more urbanized villages, ornamental plants mainly flowers and other species of shrubs occupied most of the housing compounds and other parts of the home garden for decorative and landscaping purposes. Fruit and shade trees as well as vegetables and aromatic plants were still widely planted in the gardens. There were clear indications to suggest that the habitat of Malay housing compounds and home gardens have undergone rapid transformation. The finding also exhibits that the processes of urbanization and industrialization in the region have inevitably changed the farming habits of the households. Modern plant species were preferred by the households for their housing compound. The modernizing habitat of the Malays indicates that the ecosystem and the way of life of the people in the region were actively changing. This undoubtedly will have some implications on the land use and socio-cultural systems of the region in the future that requires appropriate policies to address the issue